Microstructure and electrical properties of (1-x)Bi0.5(Na0.80K0.20)0.5TiO3-xLiNbO3lead-free piezoelectric ceramics - Pimpilai Wannasut (2018)
© 2015 IEEE. Lead-free piezoelectric ceramics with the formula of (1-x)Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 -xLiNbO 3 or (1-x)BNKT-xLN system, when x = 0, 0.01, 0.02, 0.03, 0.04, 0.05 and 0.06 mol fraction, were fabricated by a conventional mixed oxide method and sintered at the temperature of 1100°C for 2 h. All ceramics were focused in terms of phase, microstructure, dielectric, ferroelectric and piezoelectric properties. All samples have the density ranging of 5.50 - 5.66 g/cm 3 . X-ray diffraction pattern exhibited a single perovskite structure without any secondary phases. Scanning electron micrographs indicated a cubic-like grain shape occurred for all compositions with average grain size of 1.11 - 1.09 μm. The addition of LN also improved dielectric properties of BNKT ceramic. The maximum dielectric constant measured at room temperature was 1830 for BNKT-0.03LN sample.